1979
DOI: 10.1037/0735-7028.10.4.503
|View full text |Cite
|
Sign up to set email alerts
|

A program of psychologic service delivery in a multiple sclerosis center.

Abstract: We assert that psychologists have an important role to play in the care of the chronically ill, and that it is possible to construct programs that are workable, useful to patients, and of mutual interest to psychologists and physicians in the health care setting. We describe a program of psychological services in a multiple sclerosis center. These services are built on a theoretical model of coping, directed at education in a broad sense and at peer contact and support. We describe a program of group discussio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Knutson, 1985;Larberg & Cavallo, 1984). Pavlou et al (1979), in their programme of psychological service delivery to persons with MS, found that after a loved one receives a diagnosis of MS, caregivers experience trauma and numerous psychosocial problems related to their caregiving role including emotional distress (often referred to as chronic sorrow (Hainsworth, 1996)), managing one's life around the unpredictability and uncertainty of the disease, change in roles, relationship dif culties and lack of 'time out'. These caregiving problems have been further validated by systematic descriptive studies of the burden of small samples of MS caregivers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Knutson, 1985;Larberg & Cavallo, 1984). Pavlou et al (1979), in their programme of psychological service delivery to persons with MS, found that after a loved one receives a diagnosis of MS, caregivers experience trauma and numerous psychosocial problems related to their caregiving role including emotional distress (often referred to as chronic sorrow (Hainsworth, 1996)), managing one's life around the unpredictability and uncertainty of the disease, change in roles, relationship dif culties and lack of 'time out'. These caregiving problems have been further validated by systematic descriptive studies of the burden of small samples of MS caregivers (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As an unpredictable chronic condition with unknown prognosis, MS is experienced differently among patients [ 11 ], and family caregivers assuming responsibility for the constant care often experience emotional distress and sadness with role modifications [ 12 , 13 ]. On the other hand, patients, their spouses, and other family members face numerous economic and social challenges such as losing a job, reduced income, changes in social status, and caregiver exhaustion [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The demands of providing care to a person with MS are evident from findings showing that MS caregivers report: four times as many stress-related symptoms as the general population [3], significantly lower global life satisfaction compared to the general community [4], higher levels of stress compared to non-caregivers [5] and one third of caregivers have been shown to report clinically significant levels of distress and requests for mental health assistance [6]. In addition, studies show that caregivers report a wide range of problems related to their caregiving [7] (see review [8]).…”
Section: Introductionmentioning
confidence: 99%